Metformin as Host-Directed Therapy for TB Treatment: Scoping Review - Naicker, Nikita; Sigal, Alex; Naidoo, Kogieleum (Frontiers in Microbiology, 2020)
Tuberculosis disease caused by Mycobacterium tuberculosis remains a global health concern. Evolution of multi-drug resistant strains may cause bacterial persistence, rendering existing antibiotics ineffective. Hence, development of new or repurposing of currently approved drugs to fight Mycobacterium tuberculosis in combination with existing antibiotics is urgently needed to cure tuberculosis which is refractory to current therapy. Adjunctive host-directed therapies have the potential to shorten tuberculosis treatment duration and reduce lung injury by attenuating host mechanisms that cause lung inflammation. The range of potential candidates is broad, and includes several agents approved for the treatment of other diseases. One potential candidate is metformin, an FDA-approved drug used to treat type 2 diabetes mellitus. However, there is a scarcity of evidence supporting the biological basis for the effect of metformin as host-directed therapy for tuberculosis. This scoping review summarizes the current body of evidence and outlines scientific gaps that need to be addressed in determining the potential role of metformin as host directed therapy.